Reconfiguration of the State or corrupt influeces?: An analysis of the judicial collapse in Callao – Peru (2018) - Guillén Hernández, Renzo Alonso (2019)
This text tries to address the phenomenon of corruption, from the case of the "Cuellos Blancos del Puerto" from a novel approach of state capture that has the purpose of the Co-State Reconfiguration of the State (RCdE), based on structural factors and the specific particularity of the actors in the network and their activities demonstrated in the empirical evidence; In order to sustain this approach, a conceptual analysis of the notions of organized crime as opposed to that of illicit networks is carried out; the one of corrupt influences and capture of the State for which a brief review of the theories that support these phenomena is made. Thus, the text offers a formal response to a phenomenon of which very little is known and even less is analyzed: it is a first approximation, which is expected to generate more complex insights in other investigations.